Yield and Nutrient Uptake Influenced by Tillage Crop Establishment and Residue Management in Rice-Wheat Cropping System - Dudwal, B. L.; Das, T. K.; Dudwal, S. K. (International Journal of Economic Plants, 2023)
The field experiments were conducted during rainy season (June to October) and winter season (November to April) of 2010−11 and 2011−12 at the research farm of Indian Agricultural Research Institute, New Delhi to assess the effect of tillage and residue management practices on yields and nurient uptake by crops in rice –wheat cropping system. Direct seeding under unpuddled condition, transplanting under puddled condition, brown manuring and mungbean residue incorporation before sowing of direct-seeded rice were practiced in rice, while zero-till sowing, conventional till sowing and rice residue application with zero-till wheat were tested in wheat crop. During first year nutrient uptake under transplanted rice was significantly higher than the rest of the treatments. In second year, treatments where rice residue was applied in previous season wheat crop and mungbean residue incorporation showed comparable N, P and K uptake with the TPR treatments. In case of wheat the uptake of nutrients were not significantly influenced during first year of study but in second year, the treatments where rice residue was applied with zero-till wheat and mungbean residue was incorporated in previous DSR showed significantly higher N, P and K uptake. In first year of study TPR produced significantly higher yield (5.37 t ha-1) while in second year mungbean residue incorporation with direct seeded rice produced significantly at par yield (5.61 t ha-1) than the transplanted rice (5.75 t ha-1). Productivity of wheat under all the treatments during first year remained at par but in second year MBR+DSR-ZTW+RR-MB produced significantly highest yield (5.33 t ha-1).